2015
DOI: 10.1021/acs.inorgchem.5b01584
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic and Structural Studies of Mixed Sodium Bis(trimethylsilyl)amide/Sodium Halide Aggregates in the Presence of η2-N,N-, η3-N,N,N/N,O,N-, and η4-N,N,N,N-Donor Ligands

Abstract: When n-hexane solutions of an excess of sodium bis(trimethylsilyl)amide (NaHMDS) are combined with cesium halide (halide = Cl, Br, or I) in the presence of the tetradentate donor molecule [tris[2-(dimethylamino)ethyl]amine] (Me6TREN), the isolation and characterization of a series of sodium amide/sodium halide mixed aggregates was forthcoming. Cesium halide was employed because it efficiently reacted with NaHMDS to produce a molecular, soluble source of sodium halide salt (which was subsequently captured by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 76 publications
1
6
1
Order By: Relevance
“…This screen led to the identification of NaN(SiMe 3 ) 2 as a promising base, affording the product 3aa in 47% assay yield (entry 2). It is known that K + forms the stronger cation–π interactions in solution in the series Li + , Na + , and K + 39 , 40 ; however, under our conditions the potassium amide was not as successful as NaN(SiMe 3 ) 2 (entry 3 vs. 2). This may be because KN(SiMe 3 ) 2 is less efficient in the formation of the aldimine 37 .…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…This screen led to the identification of NaN(SiMe 3 ) 2 as a promising base, affording the product 3aa in 47% assay yield (entry 2). It is known that K + forms the stronger cation–π interactions in solution in the series Li + , Na + , and K + 39 , 40 ; however, under our conditions the potassium amide was not as successful as NaN(SiMe 3 ) 2 (entry 3 vs. 2). This may be because KN(SiMe 3 ) 2 is less efficient in the formation of the aldimine 37 .…”
Section: Resultscontrasting
confidence: 58%
“…It can be prepared, of course, but this would make the methods that require its use less attractive. O’Hara and co-workers found that CsN(SiMe 3 ) 2 could be generated by mixing NaN(SiMe 3 ) 2 with CsX (X = Cl, Br, or I) 40 . Furthermore, combining CsN(SiMe 3 ) 2 with equimolar NaN(SiMe 3 ) 2 led to formation of a sodium–cesium amide polymer [toluene•CsNa(N(SiMe 3 ) 2 ) 2 ] ∞ 39 .…”
Section: Resultsmentioning
confidence: 99%
“…Its solubility, stability, and commercial availability appeal to synthetic chemists and render NaHMDS an attractive target for studying aggregation and solvation. Aside from NaHMDS crystal structures of potential interest to synthetic chemists (Chart ), there are remarkably few physicochemical studies of NaHMDS in solution. , Even the computational community has shown little interest …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the reaction becomes homogeneous at approximately 50% conversion. Although, in principle, this could reflect the solubility limit of NaDA solvated by epoxide 15 , we suspect that soluble mixed aggregates are involved …”
Section: Resultsmentioning
confidence: 99%